Comparison of CDH1 Penetrance Estimates in Clinically Ascertained Families vs Families Ascertained for Multiple Gastric Cancers - Roberts, Maegan E. (JAMA Oncol, 2019)
IMPORTANCE: CDH1 pathogenic variants have been estimated to confer a 40% to 70% and 56% to 83% lifetime risk for gastric cancer in men and women, respectively. These are likely to be overestimates owing to ascertainment of families with multiple cases of gastric cancer. To our knowledge, there are no penetrance estimates for CDH1 without this ascertainment bias. OBJECTIVE: To estimate CDH1 penetrance in a patient cohort not exclusively ascertained based on strict hereditary diffuse gastric cancer (HDGC) criteria. DESIGN, SETTING, AND PARTICIPANTS: Retrospective review of 75 families found to have pathogenic variants in CDH1 through clinical ascertainment and multigene panel testing at a large commercial diagnostic laboratory from August 5, 2013, to June 30, 2018. CDH1 pathogenic variants were identified in 238 individuals from 75 families. Pedigrees from those families included cancer status for 1679 relatives. Penetrance estimates are based on 41 families for which completed pedigrees were available. MAIN OUTCOMES AND MEASURES: Gastric cancer standardized incidence ratio estimates relative to Surveillance, Epidemiology, and End Results (SEER) Program incidence for pathogenic CDH1 variants from families ascertained without regard to HDGC criteria. RESULTS: Among the 238 individuals with a CDH1 pathogenic variant, mean (SD) age was 49.3 (18.1) years and 63.4% were female. Ethnicity was reported for 67 of 75 (89%) families; of these 67 families, 51 (76%) reported European ancestry, whereas Asian, African, Latino, and 2 or more ancestries were reported for 4 families (6%) each. Standardized incidence ratios for gastric and breast cancer were significantly elevated above SEER incidence. Extrapolated cumulative incidence of gastric cancer at age 80 years was 42% (95% CI, 30%-56%) for men and 33% (95% CI, 21%-43%) for women with pathogenic variants in CDH1, whereas cumulative incidence of female breast cancer was estimated at 55% (95% CI, 39%-68%). International Gastric Cancer Linkage Consortium criteria were met in 25 of the 75 (33%) families; however, dispensing with the requirement of confirmation of HDGC histologic subtype, 43 (57%) would meet criteria. CONCLUSIONS AND RELEVANCE: The cumulative incidence of gastric cancer for individuals with pathogenic variants in CDH1 is significantly lower than previously described. Because prophylactic gastrectomy can have bearing upon both physical and psychological health, further discussion is warranted to assess whether this surgical recommendation is appropriate for all individuals with pathogenic variants in CDH1.